Airway manifestations of sarcoidosis in adolescents. Issue 10 (7th August 2020) - Obsekov, Vladislav; Chen, Linda; Pirzada, Melodi; Giusti, Robert; Kazachkov, Mikhail
Abstract: Endobronchial sarcoid lesions have previously been described and visualized upon bronchoscopy in adult patients with pulmonary sarcoid involvement. Endobronchial ultrasound‐guided transbronchial fine‐needle aspiration (EBUS‐TBNA) has come into favor as the preferred method of diagnosis, but it remains a novel technique in pediatric pulmonology. We describe the first two known cases of visualized endobronchial sarcoid lesions in the pediatric population with pathological confirmation of sarcoidosis with endobronchial and EBUS‐TBNA biopsies.